Perlindungan Hak Ulayat Masyarakat Adat; Sebuah Tinjauan Kebijakan Di Tingkat Daerah (Provinsi Banten) Untuk Pertanian Berkelanjutan - Mirajiani Mirajiani (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Banten Province has several groups of Indigenous Peoples including: 1) Baduy Indigenous Peoples, 2) Kasepuhan Indigenous Peoples. These Indigenous Peoples have the protection of the Customary Rights of the Indigenous Peoples as a Policy Review at the Regional Level for Sustainable Agriculture. Efforts to achieve sustainable agriculture must involve all citizens and all elements of society, including indigenous peoples whose existence has been recognized by international law and Indonesian law. The Provincial Government of Banten, particularly the Regional Government of Lebak Regency, has issued two regional regulations that have legal force, namely the Lebak Regency Regulation No. 32/2001 and the Lebak Regency Regional Regulation No. 8/2015. Kasepuhan which is a customary law community in the Lebak area. The Protection Policy for the customary rights of indigenous and tribal peoples is needed to maintain the sustainability of community livelihoods.